(untitled) (Itinera, 2019)
What could happen to theatre criticism in the era of disintermediation? Theatre appears obsolete, old fashioned, and elitist. Critical attitude seems uncool in a mediasphere ruled by images and emotional responses. On the other hand, critical activity on the web is quite intense and widespread, and the community of actors and audience could give us a useful insight into the visualisation processes we are experiencing. The critic, more than a consumer, becomes a witness of the creative process and of the theatrical event.